2021
DOI: 10.1049/itr2.12097
|View full text |Cite
|
Sign up to set email alerts
|

Personalized path generation and robust H output‐feedback path following control for automated vehicles considering driving styles

Abstract: This paper proposes a personalized output‐feedback path‐following control strategy for automated vehicles. A personalized path generation approach is created to obtain the expected paths of drivers with different driving styles. Historical driving data and road features are used to calculate the waypoints that characterize driving styles. Then, a robust H∞ output‐feedback controller is designed to follow the generated paths. A solution based on matrix partition is provided to compute the output‐feedback contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Toolpath generation is a core task in computer numerical control (CNC) milling machine operations, directly impacting processing quality, efficiency, and tool lifespan (Chen et al, 2021). As a research area with tremendous potential, toolpath generation technology has been extensively explored by scholars worldwide.…”
Section: Abstract Cnc Milling Machine Toolpath Point Cloud Model Roug...mentioning
confidence: 99%
See 1 more Smart Citation
“…Toolpath generation is a core task in computer numerical control (CNC) milling machine operations, directly impacting processing quality, efficiency, and tool lifespan (Chen et al, 2021). As a research area with tremendous potential, toolpath generation technology has been extensively explored by scholars worldwide.…”
Section: Abstract Cnc Milling Machine Toolpath Point Cloud Model Roug...mentioning
confidence: 99%
“…The four-point denoising method uses a single scan line as a reference and calculates the spatial distances between consecutive points P i,j , P i,j+1 , P i,j−1 , P i,j+2 . The distance calculation between any two points is given by Formula (Chen et al, 2021).…”
Section: Denoising and Downsampling Of Point Cloud Modelsmentioning
confidence: 99%
“…Driving style analysis based on collectible data accounts for a large proportion of the analysis on driving micro intention. Llorca [78].…”
Section: Drivermentioning
confidence: 99%
“…Unsupervised learning [74] MLP-NN [75] Unsupervised learning [76] DNN, wavelet algorithm [77] Driving simulator design [78] H ∞ output feedback [79] Research for the purpose of designing insurance products or at least evaluating the risk of different driving styles Establishment of risk evaluation index system [80] Visualization of risk assessment indicators [81] MOPSO [82] BN [83] Fuzzy logic and total Bayesian theory [84] CNN and PSR [85] AHP…”
Section: Literaturementioning
confidence: 99%
“…A review of research on feedback report design found most research focusing on writing/grammar (particularly learning English as a second language, e.g., [19]), math performances (e.g., [20]), and medically related activities (such as performing CPR, e.g., [21]), with most driving-specific research being related to autonomous vehicle programming (e.g., [22]). Prior studies have shown that in order to be effective, feedback reports need to be easy to use and motivate the recipient to improve [23].…”
Section: Introductionmentioning
confidence: 99%